Studies on the virulence of Neisseria gonorrhoeae. II. Relation of susceptibility to antibiotics and resistance to phagocytosis by polymorphonuclear leukocytes - P. Tapchaisri (2018)
The susceptibility to selected antibiotics and the resistance to phagocytosis were compared in 100 isolates of N. gonorrhoeae made from males with untreated gonorrhea in Bangkok, Thailand in 1971 to 1972 and in a strain (F62) isolated in the United States in 1962. Relative antibiotic resistance was common among the local isolates: 46% resisted 0.8 μg/ml of ampicillin; 18% resisted 3.2 μg/ml of chloramphenicol; 95% resisted 0.05 μg/ml of penicillin; 59% resisted 0.8 μg/ml of tetracycline. High level resistance was not encountered. Among the resistant bacteria, resistance to multiple drugs was common. Resistance to 1 μg/ml of rifampicin was encountered in only 1 isolate. Nearly all of the current isolates had a minimal inhibitory concentration for the antibiotics greater than that of the standard strain from the United States. The present isolates were similar, however, to the reference strain in resistance to phagocytosis, a property of virulent gonococci. The magnitude of the resistance to the antibiotics was unrelated to the degree of resistance to phagocytosis.